SOME FUNERAL RITUAL TRADITIONS (ON THE EXAMPLE OF THE SOUTHERN REGIONS OF KARAKALPAKSTAN) - Kamalova Dilfuza Abdullayevna (Western European Studies, 2025)
This article discusses the funeral ceremony related to human death. It also explains some specific terms and expressions used in funeral rituals. In addition, the information on this topic is presented based on historical works and field ethnographic notes
Keywords: Types of death; eternal sleep; bedsheet